Schistosoma japonicum Infection Leads to the Reprogramming of Glucose and Lipid Metabolism in the Colon of Mice - Yang, Xiaoying; Ding, Weimin; Qian, Xinyu; Jiang, Pengfei; Chen, Qingqing; Zhang, Xin; Lu, Yang; Wu, Jiacheng; Sun, Fenfen; Pan, Zhihua; Li, Xiangyang; Pan, Wei (Frontiers in Veterinary Science, 2021)
Egg deposition of Schistosoma japonicum (S. japonicum) commonly causes inflammatory reaction, fibrosis, hyperplasia, ulceration and polyposis in colon, which poses a serious threat to human health. However, the underlying mechanism is largely neglected. Recently, the disorder of glucose and lipid metabolism has been reported to participant in the liver fibrosis induced by the parasite, which provides a novel clue for studying the intestinal pathogenic mechanism. This study focused on the metabolic reprogramming profiles of glucose and lipid in the colon of mice infected by S. japonicum. We found that S. japonicum infection shortened colonic length, impaired intestinal integrity, induced egg-granuloma and increased colonic inflammation. The key enzymes of pathways regulating glucose and lipid metabolism were upregulated in the colon of infected mice. Conversely, PTEN and its downstream signaling were significantly inhibited after infection. In line with these results, in vitro, stimulation with SEA downregulated the expression of PTEN and induced the metabolic alteration similar to the in vivo results. Meanwhile, PTEN over-expression prevented the reprogramming of glucose and lipid metabolism induced by SEA in CT-26 cells. S. japonicum infection induced the reprogramming of glucose and lipid metabolism in the colon of mice, and PTEN may play a vital role in this metabolic reprogramming. These findings provide a novel insight for the pathogenicity of S. japonicum.